Effects of aid for trade on poverty, sectoral employment and economic growth in developing countries - Yakoub, Benziane (2022)
According to the OECD Creditor Reporting System (CRS), approximately 60 donors provided a total of 409 USD billion as Aid for Trade (AfT) inflows by 2017, to assist recipient countries in constructing supply-side capability and trade-related infrastructure that they require to broaden their trade. Moreover, effective utilization of these inflows enhances growth, creates job possibilities, and reduces poverty. Despite these large amounts of AfT inflows these nations continue to experience low growth and employment rates, in addition to high poverty rates. In light of this, this study aims to assess the effects of AfT inflows on poverty, sectoral employment shares, and economic growth in these recipient countries. Two methodologies were used to achieve the stated objectives, namely the two-step system Generalized Method of Moments (GMM) approach and the panel Quantile Regression approach. The sample of the study covered 60 countries for the first and 75 for the third objectives, while the second objective covered 93 countries. The 2005-2018 time period was applied for all objectives. The empirical results of the first objective demonstrated that aggregate AfT inflows including its two categories (AfT for economic infrastructure, for productive capacity building) have positive impacts on alleviating both poverty headcount and the poverty gap ratios over the full sample, particularly the high-income recipients. In contrast, AfT for trade policy and regulations appear to reduce poverty, particularly in the highest poverty rates for low-income recipients. AfT productive capacity building appears to reduce poverty rates the most, while AfT for policy and regulations was found to have the weakest positive impact compared to the categories. Secondly, regarding the sectoral employment shares, the empirical results revealed that total AfT, AfT for economic infrastructure, and AfT for productive capacity building boost both the agricultural and industrial employment shares, particularly the industrial employment share. This effect is far larger on industrial employment share in countries that rely the most on the industry in their economy (higher-income recipients). In contrast, it is only positive in the case of agricultural employment in the countries that rely the most on agriculture (lower-income recipients). However, AfT for trade policy and regulations only benefits the industrial employment share, particularly in the low-income recipients. Furthermore, the AfT interaction with FDI only increases the agricultural employment rates in the case of the low-income recipients, and the industrial employment rates in the higher-income recipients. Lastly, the empirical findings of the third objective suggested the significant effect of aggregate AfT on the receiver countries’ economic growth, precisely, the lower-income countries. In terms of its subcategories, AfT for productive capacity building generates the largest beneficial effect on the economic growth of the receiver countries followed by AfT for trade policy and regulation, while AfT for economic infrastructure was observed to have the weakest positive effect. Furthermore, AfT interaction with institutional variables was found to be negative. However, these coefficients appear to converge towards positive in the case of countries with better institutional quality (highincome recipients). Therefore, Donors may consider providing higher AfT notably AfT for productive capacity buildings, and AfT for trade policy and regulations to improve the quality of institutions and governance in the recipient countries. Moreover, recipient countries might also strengthen their institutions and promote good governance. This would result in a more efficient allocation of AfT inflows.